Vitamin D receptor gene polymorphisms and haplotypes in the etiology of recurrent miscarriages - Hubert Wolski (Nature Portfolio, 2021)
Abstract A few years ago it was shown that disturbed metabolism of the vitamin D/receptor (VD/VDR) complex may be important in the etiology of spontaneous abortion, as well as in the etiology of recurrent miscarriages (RM). The goal of this study was to investigate the association between four maternal VDR polymorphisms as well as haplotypes settings and RM occurrence in a Polish population of women in reproductive age. A total of 230 women were recruited to this study (110 with RM, 120 consecutively recruited age-matched healthy women with at least two full-term pregnancies and with no history of miscarriages). DNA samples were genotyped for VDR polymorphisms: FokI (rs2228570), BsmI (rs1544410), ApaI (rs7975232) and TaqI (rs731236). Significant differences in genotype distributions and allele frequencies between case and control groups were observed in VDR BsmI polymorphism (GG vs. GA and AA, OR = 0.56, p = 0.036 and OR = 1.49, p = 0.035, respectively). The best evidence of an association with RM prevention was observed for the TTGT haplotype, which was more frequent among controls than cases even after permutation test (0.09 vs. 0.017, p = 0.0024). Other haplotypes were also significantly more frequent in the control group: TGT (rs7975232, rs1544410, rs2228570), TG (rs7975232, rs1544410), TTG (rs731236, rs7975232, rs1544410), TT (rs731236, rs7975232). Our research indicated the possible role of VDR BsmI genetic polymorphism in RM etiology, suggesting at the same time the active role of maternal VD metabolism and its influence on pregnancy outcome. The significant influence of several maternal haplotypes was shown to prevent RM occurrence.